Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1177/112067219600600423
|View full text |Cite
|
Sign up to set email alerts
|

Dysplastic Nevi are a Risk Factor for Uveal Melanoma

Abstract: Many studies have characterized the phenotypic features of individuals who are likely to develop cutaneous melanoma. One of the major items included in melanoma risk assessment has been the presence of clinically atypical nevi (dysplastic nevi). This study assessed the number of subjects with dysplastic nevi in groups of patients with uveal melanoma or cutaneous melanoma and in a group of volunteer controls. The SPSS program was used to calculate the odds ratios (hereafter called relative risks; RR) and 95% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 11 publications
0
24
0
1
Order By: Relevance
“…Patients with atypical cutaneous nevi are 4.36 to 10.4 times more likely to develop ocular melanoma than the average population. 26,27 Iris nevus is a risk factor for uveal melanoma in general and it is a particular risk for iris melanoma, although the rate of transformation of iris nevus into melanoma is not clearly understood. 28 In a study of 175 patients with suspicious iris nevus by Territo et al, 29 8 (5%) lesions showed clinical evidence of growth into iris melanoma at a mean follow-up of 5 years.…”
Section: Host Susceptibility Factorsmentioning
confidence: 99%
“…Patients with atypical cutaneous nevi are 4.36 to 10.4 times more likely to develop ocular melanoma than the average population. 26,27 Iris nevus is a risk factor for uveal melanoma in general and it is a particular risk for iris melanoma, although the rate of transformation of iris nevus into melanoma is not clearly understood. 28 In a study of 175 patients with suspicious iris nevus by Territo et al, 29 8 (5%) lesions showed clinical evidence of growth into iris melanoma at a mean follow-up of 5 years.…”
Section: Host Susceptibility Factorsmentioning
confidence: 99%
“…Certain skin conditions, such as dysplastic nevus syndrome and nevus of Ota, are also associated with uveal melanoma. 2 It has been theorized by some investigators that exposure to ultraviolet radiation increases the risk of this neoplasia, but this has not been definitively proven. Whereas certain somatic mutations are associated with neoplastic growth and distant metastasis, the malignancy is not inherited in a traditional genetic fashion, although it is believed that individuals who have germline breast cancer 1 (BRCA1)-associated protein 1 (BAP1) mutations are at higher risk for uveal and cutaneous melanoma as well as mesothelioma and renal cancers.…”
Section: Background and Epidemiologymentioning
confidence: 99%
“…The occurrence of ocular melanoma and cutaneous melanoma in the same patient, the incidence of cutaneous melanoma and ocular melanoma in the same family, the appearance of ocular melanoma and cutaneous melanoma in patients with atypical mole syndrome and dysplastic nevi as risk factors for uveal melanoma are documented [29, 30, 31, 32, 33]. …”
Section: Discussionmentioning
confidence: 99%